Experimental investigation on the performance of single spark ignition and twin spark ignition engine fuelled with ethanol-gasoline blends - Prashant, Jagadesh; Antony, Alappat Joseph; Khan, Sher Afghan (Penerbit Akademia Baru, 2020)
Increasing the automobile population and contamination of the atmospheric air is a significant threat to the environment. Harmful emissions from the engine exhaust have considerably increased by manifolds. To bring down the pollution rate modern world demands much cleaner combustion with lesser amounts of emissions. Many investigations on IC engines have been conducted to discover such fuels that can efficiently replace the fossil fuels, produce higher heating value, and can burn to produce lesser or no harmful exhaust emissions. Also, a large number of engine modifications are being brought about to attain optimal performance values and reduced exhaust emissions but, the demand for lesser emission is a never-ending one. The investigational iteration for producing a better engine is an unstoppable one and proceeds to the next level with a small improvement in the result. Continuing to investigate in the same direction the current experimental work, investigates the performance characteristics of a single-cylinder engine with a single spark plug ignition and twin spark ignition respectively fuelled with blends of ethanol and gasoline. The experimentation was conducted at the engine’s rated compression ratio. Engine performance characteristics were initially tested by combusting the fuel blends with only one spark plug while cutting off the second one. In the second stage of the experiment, a second spark plug additional to the earlier one was introduced into the combustion chamber. The engine’s performance characteristics were tested under the same compression ratio and with the same blends of ethanol and gasoline fuel, similar to that used in the experimentation with a single spark plug. The experimental investigation demonstrated an improvement in the performance characteristics and also a decrease in the exhaust emissions with ethanol-gasoline blends and twin spark ignition engine.